The Effect of Mixing Natural Aggregates with Artificial Aggregates on Marshall Parameters - Muhammad Riski; Febrina Dian Kurniasari; Bunyamin (Jurnal Inotera, 2021)
In general, aggregates consist of Natural Aggregates (NA) and Artificial Aggregates (AA). Artificial aggregates, such as Crushed Stone (CS), are aggregates produced through the crusher industry which has a rough and angular surface so that it has excellent adhesion to asphalt. Meanwhile, NA is an aggregate produced from a river which has a smooth and large hollow surface texture. The cost for AA is very expensive when compared to NA, so it is necessary to experiment with mixing NA and AA to minimize the use of AA. NA are obtained from Sungai Jalin, Jantho City District, Aceh Besar District. The method used refers to the specification of Bina Marga 2010 Revision four (2018) and the Indonesian National Standard (SNI). The purpose of this study was to see the effect of the combination of NA and AA as a substitute for coarse aggregate on the AC-WC concrete asphalt layer. The specimens used were 66 specimens with substitution of NA and AA into the asphalt layer were 0% NA: 100% AA, 25% NA: 75% AA, 50% NA: 50% AA, 75% NA: 25% AA, 100% NA : 0% AA. Based on the research results, the best value for the optimum marshall parameter is the substitution of 25% AA: 75% BP at asphalt content of 5.00%, the stability value is 1492.37kg with a VIM value of 3.69%, VMA 16.17%, VFA 77.88% and MQ 573.87kg / mm which have met the requirements of the 2010 Revision four (2018) Bina Marga specification.